Evaluation Of CD8+ Tumor Infiltrating Lymphocytes (TILs) Association In Gastric Adenocarcinoma In A Tertiary Care Hospital In Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Gastric cancer remains one of the most common types of cancer and a major cause of cancerrelated deaths. It ranks as the fifth most frequently diagnosed cancer and the fourth leading cause of mortality worldwide. The Tumor Microenvironment (TME) consists of tumor cells, extracellular matrix, immune cells, cytokines, and other components. Among these, immune cells- particularly T lymphocytes- plays a crucial role as regulatory factors in TME. In particular, T lymphocytes, especially CD8+ Cytotoxic T Cells (CTLs) are recognized as key anti-tumor immune cells. The aim of the study was to evaluate the expression of CD8+ tumor infiltrating lymphocytes in gastric adenocarcinoma and their association with histological grade and pathological stage.  Materials and methods: This cross-sectional observational study was conducted in the Department of Pathology, Sir Salimullah Medical College, Dhaka from March 2022 to February 2024. A total of 50 gastrectomy samples with a histologically confirmed diagnosis of gastric adenocarcinoma were included in this study. The expression of CD8+ in TILs were evaluated in formalin-fixed and paraffin embedded specimens by immunohistochemistry. The CD8+ TILs were categorized as positive and negative expressions. Histopathological results were analyzed and statistical analysis was done using Statistical Package for Social Science (version 26.0).  Results: In this study showed that among 50 cases, 68% (n=34) were male and 32% (n=16) were female. The major tumor type, poorly differentiated type of adenocarcinoma reported was 38%. CD8+ intra tumoral and stromal TIL expression was positive in 33 (66%) and 35 (61%) cases respectively. A significant association was found between intra tumoral CD8+ TILs and histological tumor grade (p value=0.037) pathological stage (pvalue = 0.005) but no significant association was seen with nodal  status  (p value =0.759). Similarly, a significant association was observed between the stromal CD8+ TILs with histologic grades (p value= 0.012) and pathological stage (p value = 0.035) but not with nodal status (p value = 0.434).  Conclusion: As part of tumor microenvironment CD8+ TIL influence the progression and differentiation of gastric adenocarcinoma. These expression levels can be utilized as indicators of biological behavior and prognosis as well as in therapeutic purpose of gastric adenocarcinoma.JCMCTA 2025 ; 36 (2) : 46-52